(3eNJGQ GdUMGMs - (3eMeO Hf CHj HcQ Hf YHO GdbGOQ GdQGRj GdMfaj, Rjf GdOjf,J (B666 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HLejY GdeMGeO Ydi LejY GdfYe bGd GdYHO GdabjQ eMeO Hf CHj HcQ Hf YHO GdbGOQ GdQGRi gPG eNJUQ ai Yde GddZI LeYJg fe cJGH GdUMGM ddEeGe CHj fUQ ESeGYjd Hf MeGO GdLhjfi hSejJg eNJGQ GdUMGM HGH GdgeRI s
(3BNQgG (B:s
(3hSbWJ Cda HGdELJeGY GdSGcfjf GdCda hGdSjf hfXjQg bhd Pi GdQeI ZdG jG CSdei jG OGQ ef Ydi GdHdi hdG RGd efgdkG HLQYGFc GdbWQ hGdMeO ddg Ydi GdJeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B112s
Keywords: (3GddZIs